Interrelationship of economic growth, poverty dynamics, and revenue generation in indonesia’s regional fiscal autonomy - Priambodo, Aji (Journal of Economics Research and Policy Studies, 2025)
This study examines the dynamic relationship between regional own-source revenue, economic growth, and poverty within the framework of Indonesia’s decentralized governance. Using the Generalized Method of Moments (GMM) to address potential endogeneity, the analysis draws on panel data covering all provinces over a recent multi-year period. The findings indicate that stronger economic growth tends to be followed by improvements in the ability of local governments to raise revenue, while higher poverty levels are associated with weaker fiscal performance. The results also point to a degree of persistence in revenue patterns from one period to the next. Model diagnostics support the reliability of the estimates. These insights underline the importance of policies that encourage sustainable economic expansion and targeted poverty alleviation as key measures to strengthen regional fiscal autonomy. The study contributes to the literature on fiscal decentralization and offers practical recommendations to enhance subnational revenue performance in developing economies.